2017
DOI: 10.1103/physrevb.96.035440
|View full text |Cite
|
Sign up to set email alerts
|

Local field enhancement and thermoplasmonics in multimodal aluminum structures

Abstract: Aluminum nanostructures have recently been at the focus of numerous studies due to their properties including oxidation stability and surface plasmon resonances covering the ultraviolet and visible spectral windows. In this article, we reveal a new facet of this metal relevant for both plasmonics purpose and photo-thermal conversion. The field distribution of high order plasmonic resonances existing in two-dimensional Al structures is studied by nonlinear photoluminescence (nPL) microscopy in a spectral region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…If the temperature increase is evaluated at sufficiently large distances to the nano-object, Eq. ( 44) is usually a good approximation also for larger metallic nano-objects [54]. "Sufficiently large distances" could mean comparable to, or larger than the size of the nanoparticle.…”
Section: Linearheat (Function)mentioning
confidence: 99%
“…If the temperature increase is evaluated at sufficiently large distances to the nano-object, Eq. ( 44) is usually a good approximation also for larger metallic nano-objects [54]. "Sufficiently large distances" could mean comparable to, or larger than the size of the nanoparticle.…”
Section: Linearheat (Function)mentioning
confidence: 99%
“…27,[36][37][38][39][40] It is also worth noting that, despite -or thanks to -its IT around 800 nm (1.55 eV) and high losses in the NIR, aluminum nanoparticles are suggested as a promising alternative for light absorption and near-field enhancement in this spectral region, as well as for designing efficient integrated thermoplasmonic devices. 17,21,26,41 Several approaches have been reported to fabricate aluminum plasmonic nanostructures like lithographic methods, [19][20][21][22][23][24][25][26][27][28][29][30][31] physical vapor deposition, [33][34][35][36]39,40,[42][43][44] cluster beam depo-sition, 45 laser ablation in liquids, 46 and wet-chemical synthesis. 37,47 However, still to this day, technical challenges make it difficult to achieve the production of ultrafine aluminum nanoparticles (< 20 nm) with controlled morphology and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its cheapness and natural abundance, the advantages of aluminum are substantial both from fundamental and applied points of view: aluminum is characterized by a great amenability to manufacturing processes and compatibility with semiconductor and nanoelectronics technologies. Moreover, owing both to its high-energy plasma frequency and the absence of IT in the visible and ultraviolet (UV) ranges, aluminum nanoparticles exhibit SPR that can be tuned over a broad spectral range from the NIR down to the deep UV (below 200 nm) with a strong size and shape dependence of the SPR wavelength. Compared to noble metals, these properties make aluminum an appealing and practical material for UV-plasmonics applications ,,, such as, for example, broadband light trapping in thin-film photovoltaic devices. , It is also worth noting that despiteor thanks toits IT around 800 nm (1.55 eV) and high losses in the NIR, aluminum nanoparticles are suggested as a promising alternative for light absorption and near-field enhancement in this spectral region as well as for designing efficient integrated thermoplasmonic devices. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] One way to overcome this issue could be utilizing higher order plasmonic modes of large aluminum nanoantennae with lower radiative and interband-damping over the optical spectra. 15,18 However, higher order plasmons are dark (sub-radiant) in nature with almost zero netdipole moment, i.e. they don't easily couple with incident photons, and therefore they are not preferred in optical applications.…”
mentioning
confidence: 99%
“…Al especially has the potential to become an excellent alternative due to its abundance, sustainability, and simple processing requirements. ,, Most importantly, Al leads over other noble metals in terms of plasma frequency that lies at a higher energy. Despite their promise, Al nanoantennae have mostly been limited to biosensing applications in the ultraviolet (UV) to blue wavelength regimes due to the inherently low quality factors ( Q ) of dipolar surface plasmons resonances ( Q : ∼ 2) in the visible range as compared to Ag ( Q : 5–10) and Au ( Q : 10–20 in red). One way to overcome this issue could be utilizing higher order plasmonic modes of large aluminum nanoantennae with lower radiative and interband damping over the optical spectra. , However, higher order plasmons are dark (subradiant) in nature with almost zero net-dipole moment, that is, they do not easily couple with incident photons, and therefore they are not preferred in optical applications . Very recently, it has been shown that the plasmonic dark modes can be bright (super-radiant) and radiative in the far-field of tightly spaced nanostructures caused by symmetry breaking, allowing us to observe strong light–matter coupling at a single molecule level. …”
mentioning
confidence: 99%